(untitled) (Scientific journal of the Fergana State University, 2024)
In the work "Guliston" it is observed that concrete and abstract nouns, basic and artificial nouns appear as nouns in compound verbs of the noun+auxiliary verb model. In the work, there are many compound verbs formed with the participation of somatic units belonging to the series of specific nouns. In the compound verbs formed with them, in most cases, the somatic unit, which acts as a part of the noun, loses its lexical meaning. Separation of compound verbs made with the participation of somatic units into internal groups, carrying out a statistical analysis determines their place in the formation of compound verbs. In most of the compound verbs made on the basis of the "somatic unit+auxiliary verb" model, the common meaning is derived from the action or state performed with the help of the part represented by the somatic unit. The semantic analysis of these verbs shows to what extent the meanings expressed by the somatic unit are involved in their semantic structure.